The perception of taxpayers towards implementation of Goods and Services Tax (GST) : A case study in Selangor and Perak / Amirul Che Hashim and Nurul Syazwani Salleh - Che Hashim, Amirul; Salleh, Nurul Syazwani (2014)
The aim of this study is to investigate the perception of taxpayers towards the implementation of Goods and Services Tax (GST) in Malaysia: A case study in Selangor and Perak. Ninety respondents in Selangor and Perak participated in the study. The multiple regressions were employed to examine the relationship between attitudes, subjective norms, perceived behavioral control and law enforcement to comply with Goods and Services Tax (GST). Result showed that subjective norms, perceived behavioral control and law enforcement were significantly and positively related to the people’s perceptions except attitudes. The result for attitudes showed that attitudes are not significantly related with the perception of taxpayers towards the implementation of Goods and Services Tax (GST) in Malaysia